Risk Mitigation of Nile Fish Cultivation (Oreochromis niloticus) Biofloc System (Case Study on the Great Biofloc Network of Ulam Tirta Fish Farm, Depok and Bogor Area) - Rahmawati, Arum Amelia (Sharia Agribusiness Journal, 2025)
ABSTRACTResearch aims to identify the causes and occurrence of risks, measure the level of risk, map the risks, determine the risk mitigation of biofloc tilapia Aquaculture process. Data analysis used severity index and probability and impact matrix methods. The data used were primary and secondary, collected through observation, interviews, questionnaires, and literature studies. Respondents totaled 12 farmers. The results showed there were 120 risk events and 52 risk causes. Validity and Reliability test results show 50 valid risk causes. Based on the results of the severity index measurement, the frequency level of risk causes is 1 category very rarely, 11 rarely, 25 quite often, and 13 often. The level of impact of risk agents is 1 small category, 13 medium, 33 large, and 3 very large. the results of risk mapping found that there were 13 dominant/extreme risk agents, 1 in seedling rearing, 3 in biofloc pond preparation, 2 in biofloc application, 1 in seed stocking, 4 in water quality management, and 2 in harvest and post-harvest. risk mitigation actions were determined through Focus Group Discussion (FGD), there are 9 priority mitigations that represent the entire process of biofoc system tilapia farming.Keywords: risk mitigation; severity index; probability and impact matrix; focus group discussion.